Diagnostic Disparity of Previous and Revised American Thoracic Society Guidelines for Idiopathic Pulmonary Fibrosis - Lee Fidler; Shane Shapera; Shikha Mittoo; Theodore K Marras (Canadian Respiratory Journal)
BACKGROUND: A revised guideline for the diagnosis of idiopathic pulmonary fibrosis (IPF) was formulated by the American Thoracic Society (ATS) in 2011 to improve disease diagnosis and provide a simplified algorithm for clinicians. The impact of these revisions on patient classification, however, remain unclear.